Mini Economica Media Komunikasi Ilmu Ekonomi : Pengaruh Jenis Inovasi Terhadap Perilaku Pembelian Produk Baru - Tamara, Ismi, Fontana, Avanti (Fakultas Ekonomi dan Bisnis Universitas Indones, 2015)
many of big company such as Blockbuster, Dell, Motorola, Sony, and Yahoo move toward the end of their business. Such phenomenon happens because they cannot adapt and follow the disruptive changes in the market. Consumer innovativeness and disruptive innovation theories implied that each early adopter of different types of innovation have different characteristics.